2020
DOI: 10.1186/s12967-020-02527-1
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a cancer stem cell-related signature for prognostic prediction in pancreatic ductal adenocarcinoma

Abstract: Background Cancer stem cells (CSCs) are crucial to the malignant behaviour and poor prognosis of pancreatic ductal adenocarcinoma (PDAC). In recent years, CSC biology has been widely studied, but practical prognostic signatures based on CSC-related genes have not been established or reported in PDAC. Methods A signature was developed and validated in seven independent PDAC datasets. The MTAB-6134 cohort was used as the training set, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 45 publications
1
19
0
Order By: Relevance
“…These findings highlighted the clinical utility of DCBLD2 in liquid biopsy. Researchers recently reported two prognostic gene signatures constructed using DCBLD2 in PDAC (Raman et al, 2018;Feng et al, 2020). The prognostic accuracy of DCBLD2 was certainly inferior to that of gene models, because accumulating evidence had demonstrated that multi-gene signatures achieved higher prognostic accuracy compared with a single gene (Beane et al, 2009;Sim et al, 2017;Schmidt et al, 2018;Huang et al, 2020;Ahluwalia et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These findings highlighted the clinical utility of DCBLD2 in liquid biopsy. Researchers recently reported two prognostic gene signatures constructed using DCBLD2 in PDAC (Raman et al, 2018;Feng et al, 2020). The prognostic accuracy of DCBLD2 was certainly inferior to that of gene models, because accumulating evidence had demonstrated that multi-gene signatures achieved higher prognostic accuracy compared with a single gene (Beane et al, 2009;Sim et al, 2017;Schmidt et al, 2018;Huang et al, 2020;Ahluwalia et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from OS, we found that high expression of DCBLD2 was also indicative of short DFS. We previously reported that DCBLD2 was overexpressed in pancreatic cancer stem cells ( Feng et al, 2020 ), a small population of cancer cells with an indispensable role for tumor metastasis and recurrence ( Hermann et al, 2007 ; Simeone, 2008 ). These results suggested that DCBLD2 was potentially involved in the regulation of cell stemness and might serve as a promising therapeutic target for PDAC.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations